Tripuri Phonetic Reader - Karapurkar, Pushpa (Central Institute of Indian Languages Mysore, 1972)
Tripura Phonetic Reader helps the learners of the language to understand the scientific pronunciation methods and patterns of the language.
Keywords: Kokborok; Tripuri; Phonetic Reader; Bharatavani; Knowledge Through Indian Languages; Phonetic Reader; English